2021
DOI: 10.1016/j.clnesp.2021.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Are history of dietary intake and food habits of patients with clinical symptoms of COVID 19 different from healthy controls? A case–control study

Abstract: Background: Coronavirus disease 2019 (COVID-19) is an infectious disease that put unprecedented significant strain on clinical services and healthcare systems. The aim of the present research was to assess dietary food groups and also food habits of patients with clinical symptoms of COVID 19 and healthy controls. Methods: This caseecontrol research was carried out on 505 participants (279 subjects with clinical symptoms of COVID-19 and 226 controls), in age 18e65 years. Dietary food group's intake last year w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
1
7
1
1
Order By: Relevance
“…There is scarce evidence on these associations. The effect of dairy on COVID-19 is greatly focused on fermented dairy products, mainly on those including probiotics, which is not consistent with our results, and are associated with an enhanced immunity and lower risk of infectious diseases, including COVID-19 (mainly based on the modulation of intestinal microbiome) ( 15 , 16 , 30 , 35 , 47 , 48 ). Similarly, there is evidence on the immune modulatory role of raw cow's milk on respiratory infections ( 49 ), and even a recent publication has also shown activity against SARS-CoV-2 of some milk-derived bioactive peptides ( 47 , 50 ).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…There is scarce evidence on these associations. The effect of dairy on COVID-19 is greatly focused on fermented dairy products, mainly on those including probiotics, which is not consistent with our results, and are associated with an enhanced immunity and lower risk of infectious diseases, including COVID-19 (mainly based on the modulation of intestinal microbiome) ( 15 , 16 , 30 , 35 , 47 , 48 ). Similarly, there is evidence on the immune modulatory role of raw cow's milk on respiratory infections ( 49 ), and even a recent publication has also shown activity against SARS-CoV-2 of some milk-derived bioactive peptides ( 47 , 50 ).…”
Section: Discussioncontrasting
confidence: 86%
“…Afterwards, the antioxidant, antiinflammatory, and antiviral activities of some nutrients and foods have been evaluated (6,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Less evidence is available for the effect of complete dietary patterns on COVID-19 (4,32,(34)(35)(36)(37)(38), and most published reports on dietary patterns are related to the changes in diet caused by the pandemic or the lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…Such findings justified the hypothesis of probable protective effects of antioxidants and angiotensin-converting enzyme (ACE)-inhibitory peptides present in fermented foods that could affect COVID-19 presentation and outcome. More recently, a case–control study including 505 participants suggested that dietary intake of dough and yogurt is able to play a significant protective role by limiting COVID-19 incidence (Odds ratios 0.62, 95%-confidence [0.44-0.87] and 0.74 [0.56-0.98], respectively) ( Mohseni et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study with 200 COVID-19 patients reported that after a year of consumption of yogurt it was reported to be negatively associated to the severity of COVID-19 [157]. An additional study investigating diet reported that consumption of yogurt was associated with decreased incidence of COVID-19 infections [158]. A novel formulation formulated with Bifidobacterium animalis ssp.…”
Section: Fermented Milk Productsmentioning
confidence: 99%